Ez-warsh Mobile App Design For Teaching And Learning The Science Of Qiraat - Hayati Hussin; Muhammad Hafiz Saleh; Zainora Daud; Khairul Anuar Mohamad; Abdul Rahim Ahmad (Istanbul Aydın University, 2024)
The science of Qiraat is one of the historical glories in the Islamic history to be proud of, and it is still learned until today. It’s learning and teaching process remains conventionally. Besides that, this knowledge is spread out for certain groups of students especially those who are from the field of tahfiz al-Quran. Consequently, it has led towards an ignorance phenomenon of this knowledge among the community. The various styles of qiraat recitation could also lead to confusion and divergence among the society. Thus, this study aims to introduce a mobile application which has been developed by integrating the elements of naqli and aqli knowledge as an effort to introduce the recitation of riwayat Warsh to the Muslim society. The methodology used is qualitative and applied content analysis method and the mobile app design. As a result, a mobile app for teaching and learning the science of Qiraat on riwayat Warsh named EZ-WARSH has successfully developed in Malay language. Though, it still needs some more time to ensure that it could work effectively. This study could contribute towards the new learning method known as M-Learning among students in the public and private institutions as well as the Muslim society.